Quality of and Recommendations for Relevant Clinical Practice Guidelines for COVID-19 Management: A Systematic Review and Critical Appraisal - Wang, Yun-Yun; Huang, Qiao; Shen, Quan; Zi, Hao; Li, Bing-Hui; Li, Ming-Zhen; He, Shao-Hua; Zeng, Xian-Tao; Yao, Xiaomei; Jin, Ying-Hui (Frontiers in Medicine, 2021)
Background: The morbidity and mortality of coronavirus disease 2019 (COVID-19) are still increasing. This study aimed to assess the quality of COVID-19 relevant clinical practice guidelines (CPGs), and to compare the similarities and differences among recommendations. Methods: A comprehensively search was conducted using electronic databases (PubMed, Embase, Web of Science), representative guidelines repositories from December 1, 2019 to August 11, 2020 (updated to April 5, 2021) to obtain eligible CPGs. The Appraisal of Guidelines for Research and Evaluation (AGREE II) tool was used to evaluate the quality of CPGs. Four authors extracted relevant information and completed data extraction forms. All data were analyzed using R version 3.6.0 software. Results: 39 CPGs were identified and the quality was not encouragingly high. The median score (interquartile range, IQR) of every domain from AGREE II for evidence-based CPGs (EB-CPGs) versus (vs.) consensus-based CPG (CB-CPGs) was 81.94% (75.00-84.72) vs. 58.33% (52.78-68.06) in scope and purpose, 59.72% (38.89-75.00) vs. 36.11% (33.33-36.11) in stakeholder involvement, 64.58% (32.29-71.88) vs. 22.92% (16.67-26.56) in rigour of development, 75.00% (52.78-86.81) vs. 52.78% (50.00-63.89) in clarity of presentation, 40.63% (22.40-62.50) vs. 20.83% (13.54-25.00) in applicability, and 58.33% (50.00-100.00) vs. 50.00% (50.00-77.08) in editorial independence, respectively. The methodological quality of EB-CPGs were significantly superior to the CB-CPGs in the majority of domains (P < 0.05). There was no agreement on diagnosis criteria of COVID-19. But a few guidelines show Remdesivir may be beneficial for the patients, hydroxychloroquine +/-azithromycin may not, and there were more consistent suggestions on discharge management. For instance, after discharge, isolation management and health status monitoring may be continued. Conclusions: In general, the methodological quality of EB-CPGs is greater than CB-CPGs. However, it is still required to be further improved. Besides, the consistency of COVID-19 recommendations on topics such as diagnosis criteria is different. Of them, hydroxychloroquine +/-azithromycin may be not beneficial to treat patients with COVID-19, but remdesivir may be a favourable risk-benefit in severe COVID-19 infection; isolation management and health status monitoring after discharge may be still necessary. Chemoprophylaxis including SARS-CoV 2 vaccines and antiviral drugs of COVID-19 still need more trials to confirm.